(untitled) (GENDER EQUALITY: International Journal of Child and Gender Studies, 2019)
Early childhood education is part of the application of lifelong education (life long education) which is the main portal towards the next level of education. There are 3 different environment that is very influential for the psychology and development of children. That is; first, the family environment is the main pillar to form the good and bad of the human person to develop well in ethics, morals, and morals, if not guarded properly, the effect can be prolonged. the family environment is also the initial formation of the person and character. Children’s education requires an environment where he can develop the strengths he has brought from birth. Second, PAUD environment which is a place of education for children, PAUD environment should be fun for children and also provide opportunities for the development of the potential of each individual. Third, the environment of the wider community has a major influence on the successful planting of aesthetic values and ethics for character building. In the psychology of physical growth, cognitive development and psychosocial development of children from an early age are very important to be stimulated, so that children can develop according to their capacity.